2018
DOI: 10.1186/s13661-018-1068-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of solutions for a quasilinear elliptic equation with ( p , q ) $(p,q)$ -Laplacian and critical exponent on R N $\mathbb{R}^{N}$

Abstract: The multiplicity of solutions for a (p, q)-Laplacian equation involving critical exponent p uq u = λV(x)|u| k-2 u + K(x)|u| p *-2 u, x ∈ R N is considered. By variational methods and the concentration-compactness principle, we prove that the problem possesses infinitely many weak solutions with negative energy for λ ∈ (0, λ *). Moreover, the existence of infinitely many solutions with positive energy is also given for all λ > 0 under suitable conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Hence even in the class of convex domains, no maximizer exists for κ 1 (•) prescribing volume. Nevertheless, it is shown in [12] that ball is the unique maximizer of κ 2 (•). This makes the study of (1.11) and its more general form (1.1) more interesting.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Hence even in the class of convex domains, no maximizer exists for κ 1 (•) prescribing volume. Nevertheless, it is shown in [12] that ball is the unique maximizer of κ 2 (•). This makes the study of (1.11) and its more general form (1.1) more interesting.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Ln(n=0)$L_n(n=0)$ regularization finds broad utilization in variable selection and feature extraction, which generates the sparsest solutions, yet these sparse solutions are often challenging to compute. [ 30,31 ] To overcome this challenge, Ln(n=1)$L_n(n=1)$ regularization is introduced, but it does not exhibit sparsity as strong as L 0 regularization. [ 32 ] It is indicated that Ln(0<n<1)$L_n(0&lt;n&lt;1)$ regularization assures the generation of sparser solutions in comparison to L 1 regularization, where the index 1/2 assumes a representative role.…”
Section: Introductionmentioning
confidence: 99%
“…Using critical point theory with truncation arguments and comparison principle authors also proved bifurcation type result. For (p, q)-Laplacian problem with concave-convex nonlinearities in R n we refer to [31].…”
Section: Introductionmentioning
confidence: 99%